(untitled) (ModaPalavra e-periódico, 2026)
The present research aims to analyze the representation of human body diversity in avatars of 3D modeling systems designed for the fashion market, emphasizing the inclusion of different ethnicities and body types. Based on a traditional literature review, it adopts the methodology of visual message analysis proposed by Sanches (2017; 2012) to examine social media publications, such as Instagram and LinkedIn, using a qualitative and descriptive approach. The analysis of the results highlights the growing popularity of 3D fashion, the perspective of color-blind intersectionality, and digital exclusion resulting from the lack of representativity in available avatars. Furthermore, the predominance of Eurocentric beauty standards is observed in the construction of these avatars, with limited diversity in terms of skin color and physical features. Finally, the research emphasizes the urgent need for greater inclusion and plural representation in digital fashion, suggesting that designers and 3D artists adopt practices that better reflect the diversity of contemporary society.